2007
DOI: 10.1111/j.1365-2036.2007.03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal hypersensitivity is associated with features of psychiatric disorders and the irritable bowel syndrome

Abstract: SUMMARY BackgroundTwenty per cent of patients with heartburn do not respond to proton pump inhibitors (PPIs). Many have normal oesophageal acid exposure. We hypothesized that such PPI non-responders have heightened oesophageal sensation, and that oesophageal hypersensitivity is associated with psychiatric features including somatization and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 35 publications
1
28
0
2
Order By: Relevance
“…37 Presently, functional heartburn patients account for most of those who fail PPI treatment. 38,39 Rubenstein et al 40 have also demonstrated that GERD patients have a higher level of somatization and anxiety as compared to normal controls. In addition, psychiatric disorders were associated with lower perception thresholds for oesophageal acid perfusion and balloon distention.…”
Section: Psychological Comorbidity and Gerd Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Presently, functional heartburn patients account for most of those who fail PPI treatment. 38,39 Rubenstein et al 40 have also demonstrated that GERD patients have a higher level of somatization and anxiety as compared to normal controls. In addition, psychiatric disorders were associated with lower perception thresholds for oesophageal acid perfusion and balloon distention.…”
Section: Psychological Comorbidity and Gerd Treatmentmentioning
confidence: 99%
“…40,41 GERD patients who also had irritable bowel syndrome perceived their symptoms as more severe and tended not to achieve the same degree of improvement in GERD symptoms while treated with a PPI as those without irritable bowel syndrome. 41 Based on recent data about the contribution of psychological comorbidity to the PPI failure phenomenon, GERD patients who are not responsive to treatment should be evaluated for psychological comorbidity.…”
Section: Psychological Comorbidity and Gerd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While the data are limited, several studies have suggested that the presence of psychological comorbidity adversely affects the response of patients to proton pump inhibitor (PPI) treatment. High levels of anxiety and depression reduce the likelihood of achieving complete heartburn relief [18,19]. Moreover, the level of psychological distress is an independent predictor for poor response to PPI treatment [20].…”
mentioning
confidence: 99%
“…52 Anxiety and depression have been shown to increase GERD-related symptoms report in population-based studies. Nojkov et al provided the first evidence that response to PPI treatment may be dependent on the level of psychological distress.…”
Section: Psychological Treatmentmentioning
confidence: 99%